Monarchy in South-East Asia : the faces of tradition in transition - Kershaw, Roger (Politics in Asia series., 2001)
This book is the first study to relate the political history of the South East Asian Monarchy to the politics of the region today. The excellent coverage of this fascinating subject should be of interest to the general reader.